Study of optical, structural and electrical properties of copper oxide films prepared by chemical bath deposition with laser at different concentrations - Mohammed A. Jabr; Abdullah M. Ali; Raid A. Ismail (Tikrit Journal of Pure Science, 2023)
In this study, a copper oxide (CuO) thin film was prepared by the (Continuous-Wave) CW laser assisted-chemical bath deposition (LACBD) technique. The effect of laser wavelength on the structural, optical, and electrical properties of CuO film was investigated. The X-ray diffraction (XRD) study shows that the deposited CuO films are crystalline with a monoclinic structure. The optical energy gap increases with the use of a laser during film preparation and it varies from 2.3 to 1.8 eV. The scanning electron microscope (SEM) images confirm that the morphology of the film was dependent on the laser wavelength. Increasing the laser wavelength results in decreasing the grain size of the film which enhancing the crystallization. Energy dispersive X-ray (EDX) analysis confirms the presence of copper and oxygen elements.  Hall measurement revealed that the deposited films are p-type and the electrical conductivity and mobility increased with the use of a laser. The current-voltage characteristics of the p-CuO/p-Si heterojunction were studied in the dark and under illumination. The maximum optical current of the prepared photodetector at a laser wavelength of 550 nm was found to be in the order of 1.59 × 1012 cm.Hz1/2.W-1. The spectral responsivity revealed that the photodetectors exhibit two peaks of response at 450 nm and 800 nm. The maximum responsivity reached was 0.48 A/W at 450 nm and 0.53 A/W at 800 nm for a photodetector prepared at the laser wavelength of 550 nm.